Research on the relationship between college students' employability and IT skills training based on mixed research methods - Peng, Jiao; Deng, Chao (Frontiers in Psychology, 2022)
Information technology (IT) skills training can improve student employability. In the Internet era, there is a mismatch between the skill demands of the IT industry in China and the employment prospects of computer science graduates. The COVID-19 pandemic has particularly highlighted co-existing challenges for industry recruitment and student employment. Many education institutions see IT skills training as a way to solve this conflict. The present paper employs a mixed methods approach to explore factors regarding computer science students’ employability. The study used a questionnaire informed by an in-depth literature review, full scale development theory and the theory of competency-based education. Reliability analysis and factor analysis methods were used to assess component reliability and structural validity. A total of 323 valid questionnaires were collected and subjected to mean and variance analyses to explore significant differences, including in terms of gender, in student employability. The results show that: (1) employability is divided into nine factors; (2) IT skills training can improve employability; (3) the employability level of computer science students who participate in IT skills training is high; (4) there are significant gender differences in professional ethics, scientific spirit and job-seeking skills, but no significant gender differences in humanistic qualities, computer cognition and operation skills, software design and development skills, system use and innovation skills, sustainable development capacity and teamwork skills. The identification of student employability factors can help education institutions to improve their training and can be used as a standard for students’ self-evaluation and self-improvement. The paper also provides suggestions for education institutions about how to set up IT skills training programmes to enhance students’ future employment prospects in the IT industry.